2016
DOI: 10.1159/000445344
|View full text |Cite
|
Sign up to set email alerts
|

Audiological Results and Quality of Life of Sophono Alpha 2 Transcutaneous Bone-Anchored Implant Users in Single-Sided Deafness

Abstract: Single-sided deafness (SSD) represents one of the most difficult audiological conditions to rehabilitate. The aim of this prospective study was to evaluate the audiological benefits and quality of life of patients affected by SSD who had previously been users of the Alpha 1® when upgrading them to the Sophono Alpha 2® external processor (Boulder, Colo., USA). Nine patients were included in the study. They underwent physical examination, free-field speech audiometry at 40 and 60 dB, a hearing-in-noise test (Hir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
1
3
0
4
Order By: Relevance
“…No se observaron complicaciones mayores, y solo el 18 % de los pacientes presentaron complicaciones menores. Las complicaciones se presentaron principalmente en los pacientes manejados con Baha®, quienes experimentaron dolor local tardío, falla en la cicatrización o vértigo; estos resultados son comparables con los identificados en la literatura (15)(16)(17)19).…”
Section: Resultados De Adherenciaunclassified
See 3 more Smart Citations
“…No se observaron complicaciones mayores, y solo el 18 % de los pacientes presentaron complicaciones menores. Las complicaciones se presentaron principalmente en los pacientes manejados con Baha®, quienes experimentaron dolor local tardío, falla en la cicatrización o vértigo; estos resultados son comparables con los identificados en la literatura (15)(16)(17)19).…”
Section: Resultados De Adherenciaunclassified
“…Debido al tipo de cirugía y a la patología, este no es un cambio esperable para este tipo de pacientes (14). Los resultados obtenidos en el GBI total y sus subescalas asociados con el uso de dispositivos de conducción ósea son consistentes con lo encontrado en la literatura (14)(15)(16)(17)(18)(19)(20).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…The average score after wearing SoundBite was 31 ± 12. A previous study using GBI to evaluate the life quality showed that GBI questionnaire total score with the Sophono Alpha 2 transcutaneous bone-anchored sound processor was 14 ± 11.0, with subscale general situation score 18 ± 18.3, social support score 18 ± 22.7, and physical health score −4 ± 11.1 [ 37 ]. The scores in all aspects were worse than those of the SoundBite in this study, especially for the impact of hearing aids on physical health.…”
Section: Discussionmentioning
confidence: 99%